Penegakan Hukum Tindak Pidana Pencucian Uang dalam Pemulihan Ekonomi Pasca Pandemi Covid-19 - Sukamarriko Andrikasmi (Fakultas Hukum Universitas Riau, 2022)
The disruption to the economy and health caused by Covid 19 is used as an opportunity for money laundering crimes, especially cases of money laundering crimes that are increasing. Covid-19 should be a moment to realize the weakness of the law so that it requires a system that provides a refresher in practice, because even during normal times law enforcement experiences obstacles. Legal reforms are needed in accordance with the needs and conditions both during the pandemic and endemic, including technological developments in law enforcement, Formation of government regulations in lieu of laws, Improving the quality and competence of law enforcement officers, Training, improving law enforcement education, Law discovery by judges, increasing community participation, and modernizing law enforcement. During the COVID-19 pandemic or post-pandemic, economic growth must be balanced with efforts to implement law enforcement. The combination of law enforcement and economic rescue must become a strong model of law enforcement together, to realize the ideals of a just, prosperous, and prosperous society, as well as the goals of law in society.